Transcriptive and mental evidence on the prohibition of hoarding money and its impact on the fight against unemployment - Elkhayali, Abdellatif Mohamed (Journal of Economic, Administrative and Legal Sciences, 2022)
The issue of liquidity is one of the biggest problems that stands in the face of investment. Economic schools tried to fight it by all means, however they did not achieve what they wanted, including usurious interest as a reward for putting money in banks, so fight hoarding money, indeed a number of economists including Giselle went to claim a tax on money « stamped money », this experiment has been applied in some cities and has achieved good results. So how Islamic Sharia has treated this major problem, that stands in the face of any economic growth? The researcher in the economy when examining the ruling on hoarding money in the Islamic jurisprudence, he is surprised to find that the majority of islamic jurists say that hoarding money is permissible if the Zakat is paid, which is established in our minds, but when looking for a solution to the unemployment problem at economic schools, you find that this satatment is not in line with the purposes of Sharia, which urges work, trade and spending in order to provide a decent life for membre of nation, especially as we see what the Islamic country is living from crises because of unemployment, which is reason to spread ethical deviations, and various types of crimes, which calls for reconsidering of the rule of hoarding money, which I tried to do, to make it clear that there is no proper proof of the Prophet’s Sunnah supported the opinion of the majority of jurists, according to what I found in this research, which was considered a spark to raise the research by a specialized jurists, ALLAH bless him from his wisdom.